The Potential of Medical Tourist\'s attraction in Hospitals (A Case Study of a Military Hospitals in Tehran) - Sayed Masood Mosavi-negad; Omid Adeli; Tahere Hariri; Neda Vali-pour; Zahra Moshkani (Tehran University of Medical Sciences, 2016)
Background: Many hospitals of Iran make use of their therapeutic capacities in order to attract medical tourists and increase revenue and efficiency of their affiliated hospitals. This issue has major benefits for hospital and tourists. This study assessed the potential of medical touristschr('39') attraction in a military hospital in Tehran. Materials and Methods: This was a descriptive- analytical one which used secondary data to analyze. Data gained from quality improvement and finance offices, recipients of service and health information management units from the first of 2014 to the first semester of 2015. Strategic plan document were used to analyze the opportunities and strengths points. Results: The mean of studied hospital performance indicators like bed occupancy rate, length of stay, Bed turnover, rate of admissions to bed, mortality and bedsores rates, nosocomial infections, medication error, patientschr('39') rights and patient satisfaction were  4.68 ,  3.3,  5.1 , 6.6 ,  5.2, 1,  69, 9.74 , 70 percent respectively. The strengths points of the studied hospital were diverse expertise, updated equipment and minimum waiting time. Conclusion: Because of skilled man power, physical resources and especially modern equipment, the hospital does not need huge investment in medical touristschr('39') attraction. This issue will increase admission, productivity and satisfaction of clients and staff.